Breastfeeding/ Complementary Feeding Behavior and Food Diversity of Stunting Toddlers in North Sumatra - Nasution, Zuraidah; Lubis, Zulhaida; Nurhayati, Ida; Irianti, Evi; Mahdiah, Mahdiah; Zahara, Ratna (Devotion : Journal of Research and Community Service, 2023)
SSGI (Nutritional Status Study of Indonesia) survey in 2021 found that prevalence of stunted infants in Sumatera Utara province is still higher (25.8%) than the national limit. It is known that stunting is multifactorial condition with breastmilk/weaning food feeding behavior as one of the contributing factor. Furthermore, family’s attitude toward consuming wide variety diets is also considered as factors related to stunting. Secondary data from SSGI 2021 involving 10,755 households was used in this study. STATA application was used to help analyzing the data. Statistical analysis was conducted by using Chi Square and showed that breastmilk/weaning food feeding behavior, and varied diets in family were not contributing factors of stunting in Sumatera Utara province. However, we found that educational background was significant contributing factor to stunting (p = 0.000). We suggest that other approach, such as qualitative measure may be used in future study to investigate factors attributable to stunting.